Kemampuan Matematika Siswa SMP di Provinsi Sumatera Selatan (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2023)
The mathematical abilities possessed by each student are different even though they are at the same age and at the same level of education. In order to find out students' mathematical abilities can be known based on the test results on the questions provided and given an assessment by the teacher. This study aims to determine the math abilities of junior high school students in South Sumatra Province. This research uses quantitative research methods. The sample in this study were public and private junior high schools in South Sumatra with a total of 416 students. From the results of the research conducted by researchers, it was obtained the mathematical ability scores of junior high school students in South Sumatra Province using multiple choice questions for the 2018/2019 Mathematics National Examination. A total of 416 students as the research sample, obtained a final score with a very good category of 0.4%, a good category of 51.6%, an adequate category of 40% and a poor category of 8%. The largest percentage or average final score of junior high school students in South Sumatra Province with a sample of 416 students and the 2018/2019 Mathematics National Examination questions with a total of 40 items in the Good category